EIB Working Papers 2019/08 - Investment What holds Romanian firms back? (Volume 2019/8) - Pal, Rozalia (European Investment Bank, 2019)
In Romania, the share of firms carrying out investment is amongst the lowest in the European Union. This is despite strong economic growth in recent years and persistent needs for upgrading the capital stock in the country. This paper draws on information from two surveys - the EIB Investment Survey and a survey on access to finance conducted by the National Bank of Romania - to analyse the reasons for this subdued corporate investment activity. It also contributes to the debate on why investment in central, eastern and south eastern Europe has remained relatively subdued after the crisis.